Unexpected epithelial ovarian cancers arising from presumed endometrioma: A 10-year retrospective analysis - Hsin-Hong Kuo; Chen-Ying Huang; Shir-Hwa Ueng; Kuan-Gen Huang; Chyi-Long Lee; Chih-Feng Yen (Elsevier, 2017)
Objective: To evaluate the incidence and prognosis of unexpected epithelial ovarian cancers (EOCs) occurring in presumed benign endometrioma. Materials and Methods: Patients who underwent primary surgery at Chang Gung Memorial Hospital between November 2003 and October 2013 were searched with the Systematized Nomenclature of Medicine code followed by chart review. Results: The incidence of unexpected EOCs in presumed ovarian endometrioma was 0.14%, as 11 patients were revealed after reviewing 497 patients of pathology-proven EOCs in the current series. All patients were aged ≥ 40 years; seven (63.6%) had inward mass within ovarian cyst in preoperative images, six had cancer antigen-125 (CA-125) > 200 U/mL, and two with CA-125 > 1500 U/mL. Ten patients underwent laparoscopy initially, including five with ovarian preservation at the beginning. Ten patients subsequently completed concurrent or secondary staging surgery, including four totally with laparoscopy. The histologic subtypes had clear-cell (8/11), endometrioid (1/11), mixed clear-cell and endometrioid (1/11), and low-grade serous adenocarcinoma (1/11). Seven patients had endometriosis-associated ovarian carcinoma (EAOC), while the other four were non-EAOC with no endometriosis component. The only mortality was a patient of non-EAOC in Stage IIIc, whereas the other 10 in Stage I were alive. The overall survival rate was 90.9% (10/11) with follow-up ranging from 23 months to 130 months. Conclusion: Unexpected EOCs occurring in presumed ovarian endometrioma was rare and, if present, the prognosis was good in Stage I disease with laparoscopic management. Combining parameters of patient's age, CA-125 level, and inward solid mass at imaging could help to raise the precautions.